Early Christianity and classical culture: comparative studies in honor of Abraham J. Malherbe - Fitzgerald, John T.; Olbricht, Thomas H.; White, L. Michael (Novum Testamentum / Supplements, 2003)
This volume contains 28 essays in honor of Abraham J. Malherbe, whose work has been especially influential in exploring modes of cultural interaction between early Jews and Christians and their Graeco-Roman neighbours. Following an introductory essay on the problems inherent to such comparative studies in the history of New Testament scholarship, the essays are grouped into five topic areas: Graphos - semantics and writing, Ethos - ethics and moral characterization, Logos - rhetoric and literary expression, Ethnos - self-definition and acculturation, and Nomos - law and normative values. Some key examples are studies dealing with The Greek Idea of "Divine Nature" and its relation to the "Divine Man" tradition; Compilation of Letters in Cicero's collection; Radical Altruism in Paul; Greek Ideas of Concord and Cosmic Harmony in 1 Clement; The Rhetorical Use of Friendship Motifs in Galatians in comparison with Second Sophistic Orators; Wills and Testaments in Graeco-Roman perspective.